'A City upon a Hill': The Wire and Its Distillation of the United States Polity. (October 2014) - Wheeler, Mark
The Home Box Office's series The Wire (2002–2008) provides an informed critique of the decline of the democratic American ideal of the 'city upon a hill'. From its inception as a police procedural, it expanded its interests across the dystopian city of Baltimore to consider the linkage between drug crimes, policing, the collapse of blue-collar life, social deprivation, institutional compromise, the public school system, media compliance and political self-interest. Therefore, this article will situate The Wire into the debates that have defined the US polity and will discuss how it employs the narrative conventions of a contemporary thriller to offer an alternative view of American democracy.